1984
DOI: 10.1104/pp.74.4.967
|View full text |Cite
|
Sign up to set email alerts
|

Chloroplast Structure and Starch Grain Accumulation in Leaves That Received Different Red and Far-Red Levels during Development

Abstract: The objective ofthe present study was to examine chloroplasts in leaves that developed under a common photosynthetic environment but received 5 min of R or FR light to put phytochrome in the FR-absorbing or R-absorbing form, respectively, each day at the end of the photosynthetic period. MATERIALS AND METHODSPlant Materials. Tobacco (Nicotiana tabacum L. cv Burley 21) seedlings were started and grown to transplant size in expanded peat pellets at 28C under 14-h photoperiods at 5 mw/ cm2 between 300 and 800 nm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
26
0
2

Year Published

1989
1989
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(29 citation statements)
references
References 14 publications
1
26
0
2
Order By: Relevance
“…These findings confirm those reported by KASPERBBAUER andHAMILTON (1984) andLEONG et al (1985). Red light is essential for the development of the photosynthetic apparatus and has been shown to increase the accumulation of starch in many plant species by the inhibition of translocation of photo-assimilates to other tissues (KASPERBBAUER and HAMILTON, 1984;SCHUERGER et al, 1997).…”
Section: Resultssupporting
confidence: 82%
“…These findings confirm those reported by KASPERBBAUER andHAMILTON (1984) andLEONG et al (1985). Red light is essential for the development of the photosynthetic apparatus and has been shown to increase the accumulation of starch in many plant species by the inhibition of translocation of photo-assimilates to other tissues (KASPERBBAUER and HAMILTON, 1984;SCHUERGER et al, 1997).…”
Section: Resultssupporting
confidence: 82%
“…For instance, it contains only little blue light, while it is well known that reductions in blue light lead to increased elongation . Furthermore, red light (Kasperbauer and Hamilton, 1984) and very long daily light periods increase accumulation of starch in the leaves (Dorais et al, 1996). Excess starch accumulation may occur when daily night periods become too short (< 4h) for the breakdown of starch and export of sucrose out of the leaves.…”
Section: Light Spectrum and Plant Developmentmentioning
confidence: 99%
“…At the end of the daily light period, plants were exposed to either 5 min of R (3.6 W m-2 in the 600-700 nm waveband) or to 5 min of FR (3.6 W m-2 in the 700-770 nm waveband) at 25°C, then returned in darkness to the growth chamber for the remainder of the 12-h night. The R and FR radiation units were as described in earlier studies (14). Daily R and FR treatments began when seedlings reached the unifoliolate leaf stage.…”
Section: Srid Analysismentioning
confidence: 99%
“…The present research was undertaken to study the influence of the FR/R ratio in upwardly reflected light on Chl and LHC-II content under field conditions. Controlled environment studies have shown that the ratio ofFR' relative to R light acts through the phytochrome system to regulate stem elongation (6); leaf shape, thickness, and Chl concentration (16); and chloroplast structure including the number and size of grana and the Chl a/b ratio (14). The FR/ R ratio received during leaf development has been associated with photosynthetic efficiency of the leaves (16), and phytochrome involvement in the adaptation of the photosynthetic mechanism (12,14).…”
mentioning
confidence: 99%
See 1 more Smart Citation